First Portuguese Health Examination Survey and HBM: future opportunities - Namorado, Sónia (2017)
Population based health examination surveys collect information by a detailed questionnaire complemented with objective information from physical examination and laboratory tests of biological samples. These surveys provide more accurate and better quality information for many health indicators, some of which cannot be obtained through other methods. In Portugal, population-based epidemiological studies including a physical examination component have been developed to measure the prevalence of obesity, diabetes and hypertension. Although highly relevant these studies are specific to certain specific disorders, some are not nationally representative and none of them followed the methods of the European Health Examination Survey. The First Portuguese Health Examination Survey (INSEF) is being developed as a cross-sectional population-based study representative at regional and national level that aims to expand knowledge of health status, health determinants and use of health services. By the end of INSEF a nationally representative probabilistic sample of more than 4500 individuals with the respective biological samples (whole blood, serum, plasma and DNA) and with integrated epidemiological data (physical exam and health questionnaire) will be available for future research. This presentation highlights the work already done and describes the opportunities INSEF presents and how it can contribute to the gathering of exposure data from the Portuguese population. The collected biological samples could be used for the accurate evaluation of the internal exposure of the Portuguese population to environmental chemicals such as metals/trace elements, PCBs, PFCs, PBDEs, organochlorine pesticides, flame retardants and other compounds. On the other hand, the possibility to re-contact INSEF’s participants opens a window for the collection of additional questionnaire data needed to properly interpret the biomarker values.